The Imaginary Capital: Legal Uncertainty Surrounding Sofifi as North Maluku Center of Regional Government - Gunawan A. Tauda; Andy Omara; Faiz Rahman; Abdul Kadir Bubu (APHTN-HAN, 2026)
For more than twenty-five years since its establishment, the central government has been unable to resolve the fundamental issue concerning the designation of the capital of North Maluku Province. As a result, governance and regional development have remained stagnant due to persistent legal uncertainty surrounding the status of the provincial capital. This issue is particularly critical, as it constitutes a structural and systemic problem that continues to hinder effective administration in the region. This article seeks to examine the legal and institutional complexities involved in the proposed establishment of Sofifi as a new autonomous region and its designation as the capital of North Maluku Province, as well as to interpret the legal framework set out in Article 9 paragraph (1) of the Law on North Maluku Province. The study argues that, under the current legal framework, Sofifi does not meet the requirements to function as a provincial capital, and its ambiguous status generates significant legal uncertainty, particularly in the absence of a law formally establishing Sofifi City as a new autonomous region. Accordingly, a comprehensive re-evaluation of Sofifi’s current status is necessary. To address what has been described as the problem of an “imaginary capital,” this article proposes the designation of Tidore Islands City as the center of government or the provincial capital of North Maluku Province through the enactment of a Third Amendment to the Law on North Maluku Province.